Упровадження інноваційних технологій у процесі фахової підготовки майбутніх психологів - Романовський, Олександр Георгійович (НТУ "ХПІ", 2012)
The article highlights the modern trends in the use of innovative technologies in education. The theoretical and practical aspects of game design in high school. The basic features of the game design and the experience of its use in the training of future psychologists in N T U "KPI".
Keywords: реформування вищої освіти; інтеграція; педагогічний процес